Association of sociodemographic and oncological features with decision on implant‐based versus autologous immediate postmastectomy breast reconstruction in Chinese patients. (5th April 2019) - Yin, Zhuming; Wang, Yan; Sun, Jingyan; Huang, Qingfeng; Liu, Jing; He, Shanshan; Han, Chunyong; Wang, Shu; Ding, Bowen; Yin, Jian
Abstract: Background and objectives: Immediate postmastectomy breast reconstruction (IPBR) has gained wide popularity in China. We sought to clarify the prevalence and predictors of implant‐based vs autologous IPBR among Chinese patients. Methods: A retrospective cohort study was performed using a prospectively maintained database. Women who underwent IPBR during 2001‐2017 were included. The modality‐specific trends were deciphered by curve fitting analysis. The association of sociodemographic and oncological features with the decision for implant‐based vs autologous IPBR was investigated using multivariate logistic regression and structural equation modeling. Results: Among 905 patients included in the study, 479 underwent implant‐based IPBR and 426 underwent autologous procedures. The implant/autologous ratio has increased exponentially over time. Multivariate analysis demonstrated that unmarried patients with BMI ≤ 24 kg/m 2, earlier clinical tumor stage, and preoperative pathological diagnosis of noninvasive lesion are more likely to choose implant‐based IPBR compared to autologous procedures. The indirect effects of age, mastectomy type, and neoadjuvant chemotherapy were further demonstrated by the structural equations. Conclusions: The sociodemographic and oncological features are directly or indirectly associated with the decision on type of IPBR. The findings may facilitate both patients and physicians to make a high‐quality decision by holistic evaluation of the sociodemographic and oncological features. Abstract : The retrospective cohort study demonstrates the use of implant‐based immediate postmastectomy breast reconstruction has increased exponentially over time compared with autologous paradigms in China. The sociodemographic characteristics and oncological features display direct and indirect associations with the decisions on the type of breast reconstruction among Chinese patients.